Transformasi Pembelajaran Interaktif: Inovasi Teknologi dalam Meningkatkan Keterlibatan Siswa di SMAN 2 Bangkinang Kota. - Indah Efriani Zahara; Novi Ferlinitasari; Jhon Hendro; Erlisnawati Erlisnawati; Gimin Gimin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Interactive learning through technology has become an essential element in enhancing student engagement in the digital era. This study aims to explore the implementation of interactive technology in learning at SMAN 2 Bangkinang Kota, identify its impact on student engagement, and analyze the challenges faced by teachers in adapting to these technologies. Using a qualitative approach with a case study method, this research examines the experiences of 7 teachers who actively utilize smart boards, digital platforms, and multimedia applications in their teaching. Data collection was conducted through in-depth interviews, classroom observations, and document analysis, while data analysis employed thematic analysis to identify patterns related to student engagement and technological implementation challenges. The findings reveal that interactive technology enhances student engagement in learning, particularly in terms of active participation, conceptual understanding, and independent exploration of materials. Classroom observations indicate that students learning with multimedia simulations and interactive quizzes demonstrated higher engagement levels compared to those using traditional methods. However, the study also found that teacher readiness and infrastructure limitations remain significant obstacles in optimizing technology implementation. Some teachers experience difficulties in adapting to technology, while unstable internet access frequently disrupts the smooth delivery of digital-based learning. Therefore, this research recommends the implementation of continuous training programs for teachers, improved access to technological infrastructure, and strengthened school policies to ensure effective and sustainable technology integration in education. Through a more structured implementation strategy, schools are expected to leverage interactive technology to create a more innovative, participatory, and exploratory learning environment.